Re-ignition of multi-species soot clouds in building fires - T. Poespowati; B. Moghtaderi (Reaktor, 2007)
The re-ignition potential of multi-species soot clouds in building fires were investigated  based on their extinction characteristics. The investigation was carried out theoretically using the adaptation of Semenov`s thermal explotion theory. The critical sizes of soot particles in the cloud were found to be strongly effected by  the particle temperature., shape, and reactivity, as the mass fraction of each species, and ambient conditions. The clous shape, cloud particle number density, fuel mass fraction and soot reactivity were identified as the major parameters impacting upon the cloud extinction potential. Our analysis indicate that blending of a base soot with a less reactive soot generally increases extinction potential of the cloud ( i.e. likelihood of extinction) while addition of a more reactive secondary soot to the base one minimizes the probability of cloud extinction.Keywords: extinction, clouds, re-ignition, soot